Gabriel's Story - MacRae, Ian (UnderCurrents: Journal of Critical Environmental Studies, 1999)
I once lived for a time abroad; upon my return to Canada, I was filled with the deep solitude and sense of loss of one who is shorn from language, from culture and place, from familiar ways of living and of perceiving time. [...]